2007
DOI: 10.2981/0909-6396(2007)13[258:corfvv]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Red Fox Vulpes Vulpes and Pine Marten Martes Martes Food Habits in a Deciduous Forest in Hungary

Abstract: Feeding habits and interspecific trophic niche overlap of two sympatric predators, the pine marten Martes martes and the red fox Vulpes vulpes, were studied in a deciduous forest habitat in Hungary with conditions of differing abundance and dominance in the rodent community. The main food source of the predators consisted of small mammals, mainly rodents. Consumption of small mammals was higher during bank vole Clethrionomys glareolus dominated years than in Apodemus mice dominated years. Both predators prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 52 publications
(100 reference statements)
2
31
0
1
Order By: Relevance
“…The marten's dietary composition varied seasonally, between years and in relation to village size. Many other generalist predators have shown a similar spatial and temporal flexibility of dietary composition and plasticity, in their capacity to adapt to changing abundances of food resources within the environment (Jędrzejewski and Jędrzejewska 1992;Lanszki et al 1999Lanszki et al , 2007Borkowski et al 2011;Kidawa and Kowalczyk 2011). Seasonal and inter-annual variation in dietary composition has also been observed in other martens.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The marten's dietary composition varied seasonally, between years and in relation to village size. Many other generalist predators have shown a similar spatial and temporal flexibility of dietary composition and plasticity, in their capacity to adapt to changing abundances of food resources within the environment (Jędrzejewski and Jędrzejewska 1992;Lanszki et al 1999Lanszki et al , 2007Borkowski et al 2011;Kidawa and Kowalczyk 2011). Seasonal and inter-annual variation in dietary composition has also been observed in other martens.…”
Section: Discussionmentioning
confidence: 92%
“…Seasonal and inter-annual variation in dietary composition has also been observed in other martens. Pine marten, sable (Martes zibellina) and American marten (Martes americana) diets have been shown to be primarily dependent on the abundance of rodents (Thompson and Colgan 1990;Jędrzejewski et al 1993;Helldin 1999;Zalewski 2004Zalewski , 2007Lanszki et al 2007;Dubinin 2010;Balestrieri et al 2011). In seasons, or years when abundance of their main prey is low, these marten species supplement their diet with other food sources, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be used as indirect evidence supporting the idea that foxfeeding is altering the way that red foxes use habitats in Stanhope. In Stanhope, red foxes did not show much preference for habitats such as forests, abandoned fields, and shrubs, in which they would normally have to hunt for prey such as small mammals (e.g., [16,[37][38][39][40]). Movement-segments within both dunes and human-use areas tended to be longer than in other habitat types.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that in both sites foxes used forested areas less than expected based on their availability. A possible explanation for this finding is that rodents, often a main prey of foxes (e.g., [39][40]), were more accessible in other habitat types. Several studies have shown that red fox uses forested areas significantly more than expected based on their availability mainly due to both low snow accumulation and the ability to forage for small mammals [38,41].…”
Section: Discussionmentioning
confidence: 99%